Coins saving box multifunctions / Mimi Amira Shafie … [et al.] - SHAFIE, MIMI AMIRA; RAMLI, SITI NUR ATIRAH; ISMAIL, NOOR AINUL HUSNA (2018)
The product is Coin Saving Box Multifunction. Nowadays, savings are increasingly decreasing among adolescents because saving them is not a useful thing. This product is suitable for among teenagers who are learning to saving the money to future life and interested to improve attitude of the save money everyday life. The product also can connect with application on the phone because we innovation the coin saving box to new innovation so that we add the application can connect with the coin saving box. Name the application is a KETS. KETS serves as a money store. The application is intended to encourage teenagers to save money at young time. KETS with an application that allows you check balance and set goals how much to want save money. This product more fun when user download with their apps. The product has a rechargeable battery with on onn/off.